2017
DOI: 10.18311/jbc/2016/15592
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol and growth promotive potential of <i>Streptomyces</i> spp. in black pepper (<i>Piper nigrum</i> L.)

Abstract: Actinomycetes isolated from the rhizosphere of black pepper and from vermicompost were tested for their antagonistic effect against Phytophthora capsici and Radopholus similis, the causal agents of foot rot and slow decline diseases of black pepper. Based on in vitro evaluations, four isolates were shortlisted (IISR Act2, IISR Act5, IISR Act6, and IISR Act9) and subjected to in vivo evaluation for Phytophthora infection by challenge inoculation and also greenhouse evaluation for growth promotion in black peppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Several functionalities associated with actinomycetes, especially production of indole acetic acid (IAA) might explain the increase in the nutrient content of the tomato plant. Although strain RC18 was not assayed for production of IAA which enhances uptake of nutrient by increasing the size and surface area of the root (Aeron et al, 2011), some researchers have shown that most actinomycetes can produce IAA (Anwar et al, 2016;Bhai et al, 2016).…”
Section: Plant Mineral Contentmentioning
confidence: 99%
“…Several functionalities associated with actinomycetes, especially production of indole acetic acid (IAA) might explain the increase in the nutrient content of the tomato plant. Although strain RC18 was not assayed for production of IAA which enhances uptake of nutrient by increasing the size and surface area of the root (Aeron et al, 2011), some researchers have shown that most actinomycetes can produce IAA (Anwar et al, 2016;Bhai et al, 2016).…”
Section: Plant Mineral Contentmentioning
confidence: 99%